Iridaceae endémicas del Perú - León, Blanca (2006)
The Iridaceae are represented in Peru by 14 genera and 53 species of herbs (Brako & Zarucchi, 1993). Here we recognize 16 endemic species in seven genera. We assigned IUCN threat categories to five species. Peru’s endemic taxa occupy several ecological regions, including the Subtropical Coastal Desert, Mesic Shrublands, and Humid and Dry Puna, between 2000 and 4700 m elevation. Only one endemic species has been reported from a protected area to date.